Pengaruh Pemberian Soal Matematika Jenis Open-Ended Problems Terhadap Kemampuan Siswa Memecahkan Masalah Program Linier - Nissa, Ita Chairun; Lestari, Puji; Kumala, Dian (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
[Title: The Effect of Open-Ended Problems on Mathematics Problem toward Students' Ability in Solving Linear Program Problems]. The purpose of this study is to determine whether the provision of linear program mathematical problems in the form of open-ended problems can affect students' problem-solving abilities. This research is an experiment with one sample group, 28 students of class XI IPA-2 in SMA Negeri 7 Mataram. Data was collected through tests and interviews that were statistically analyzed both descriptive and inferential. The validity of mathematical problems is based on expert judgment while the reliability is tested using product-moment correlation. Pre-test and post-test data have been tested both homogeneous and normally distributed. The homogeneity test uses the F-test statistics and the normality test uses the interpretation of skewness and kurtosis. The influence test is performed using one-party t-test statistics. Student problem-solving performance was assessed using a holistic rubric. All data is processed using data analysis tools on Microsoft Excel. This experiment showed success by obtaining an average test score of students when the pre-test was 39.58 which then increased when the post-test became 79.76. This increase was statistically significant as evidenced by the one-party t-test where tcount = 37.33> ttable = 1.67 at Î± = 0.05, which means that Ha was accepted. So it can be concluded that there is an effect of the treatment given a mathematical problem in the form of open-ended problems to the ability of students to solve linear program problems.